Graft Copolymerization of Benzyl Methacrylate onto Alginates - Shakir, Ameer Piro (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Homopolymerization of benzyl methacrylate has been studied by UV initiation using 25 mg DMPA with 2.5 ml BzMA and 0.5, 2.5 mL hexane for different time intervals. The maximum conversion value 99% has been obtained. Homopolymerization reaction was carried out with and without photo initiator. It was found that without photo initiator polymerization does not occur. DMPA and benzophenone were the two photo initiators tested. DMPA was found to be more effective than benzophenone, in a homopolymerization system of 50 mg DMPA or bezophenone, 2.5 mL BzMA and 0.5 mL hexane irradiated for 15 minutes, conversion resulted 61% and 11.5% respectively. Without photo initiator no polymerization occurred. Alginic acid, sodium alginate and calcium alginate have been grafted with poly(benzyl methacrylate) by the UV-irradiation method. The heterogeneous system was placed in a LZC4 photo-reactor with 15 cm distance from UV lamps (in UVA region, 350 nm) and irradiated for several different intervals of time, at room temperature (25±1◦C) and fixed power (7670 μW/cm2). Effect of irradiation time, monomer concentration and photo initiator concentration on the grafting yield was studied at room temperature. The maximum grafting yield was obtained using 0.52 g sodium alginate with 2.5 mL BzMA and 25 mg DMPA at 15 min. It was found that most vulnerable polymer to benzyl methacrylate grafting among alginic acid, sodium alginate and calcium alginate is sodium alginate with the highest grafting yields under the same conditions with others. Keywords: Alginate, Benzyl methacrylate, Graft copolymer, Photopolymerization

ÖZ: Benzyl metakrilatın homopolimerizasyonu ve sodyum aljinat, aljinik asit ve kalsium aljinat üzerine aşılanması foto-LZC4 reaktörü içinde 350 nm dalgaboyunda, 7670 μW/cm2 sabit güce sahip UV lambaları örnekten 15 cm uzakta konumlanmış şekilde oda sıcaklığında, farklı zaman aralıklarında çalışılmıştır. Işınlama deneyleri ya DMPA ve benzofenon olmak üzere iki farklı foto başlatıcı varlığında ya da foto başlatıcı olmadan yapılmıştır. Foto başlatıcı kullanılmadığı durumda polimerizasyon veya kopolimerizasyonun gerçekleşmediği gözlemlenmiştir. Yirmi dakika ışınlama süresi sonunda 25 mg DMPA, 2.5 mL BzMA ve 0.5 mL hekzan karışımının azami dönüşüm değeri % 99 olarak elde edilmiştir. Benzer koşullarda DMPA varlığında homopolimerizasyon dönüşüm değerinin benzofenona göre daha fazla olduğu bulunmuştur. 50 mg DMPA veya 50 mg benzofenon varlığında homopolimerizasyonun 2.5 mL BzMA ile 0.5 mL hekzan bulunduran homopolimerizasyon sisteminde 15 dakika süre ışınlama süresi sonunda . homopolimerizasyon dönüşüm değerleri sonuçları sırasıyla % 61 ve % 11.5 olarak bulunmuştur. Aljinik asit, sodyum aljinat ve kalsiyum aljinat üzerine gerşekleştirilen aşılama reaksiyonları için ışınlama süresi, monomer konsantrasyonunun ve başlatıcı konsantrasyonunun aşılama yüzdesine etkisi oda sıcaklığında incelenmiştir. En fazla aşılama verimi 39.5% 15 dakikada, 2.5 ml BzMA 25 mg DMPA varlığında 0.52 g sodyum aljinat kullanılarak elde edilmiştir. Anahtar Kelimeler: Aljinat, Benzil metakrilat, Aşı kopolimer, Fotopolimerleşme
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Chemistry; Alginate; Benzyl methacrylate; Graft copolymer; Photopolymerization